Peircean Architectonics in the Discourse and Digitalization of Interdisciplinarity - Jeremy Dennis (Journal of Interdisciplinary Sciences, 2022)
After the onset of the global pandemic in 2020, educators and policymakers are reimagining academe and its protocols and practices. Interdisciplinarity is often evoked as both a panacea and praxis in their blueprints and frameworks for a new academic architecture for higher education. However, advocates for interdisciplinarity are often unaware of the contradictions and tensions that scholars have long recognized between the rhetoric of interdisciplinarity and its actualization. As such, the troubled constitution of interdisciplinarity confuses its discourse and limits its agency, making it harder for educators and policymakers to advance a vision that is congruent with the increasing digitalization of teaching and learning in education. This theoretical meta-synthesis recalibrates the discourse of interdisciplinarity by illuminating its expression in Charles S. Peirce’s architectonic theory. By reimagining Peircean pragmatism in the epistemological genealogy of interdisciplinarity introduced by James Welch, we can posit an alternative paradigm and discourse that educators and policymakers can use to reconceive higher education.